My name is Khan - Johar, Karan, 1972-; Johar, Hiroo Yash; Dharma Productions; Red Chillies Entertainment (Firm) (Mumbai : Reliance Big Home Video, 2010)
Rizvan Khan, a Muslim from India, moves to San Francisco and lives with his brother and sister-in-law. Rizvan, who has Aspergers, fall in love with Mandira. Despite protests from his family they get marries and start a small business together. They are happy until September 11, 2001 when attitudes towards Muslims undergo a sea-change. When tragedy strikes, Mandira is devastated and they split. Rizvan is very confused and very upset that the love of his life has left him. To win her back, he embarks on a touching and inspiring journey across America.
disc 1. Movie -- disc 2. Special features.
Copyright notice on container: Dharma Productions Pvt. Ltd. & Red Chillies Entertainment.
Originally released theatrically in 2010.
Summary taken from container.
Stody & screenplay Shibani Bathija; lyrics, Niranjan Iyengar; music, Shankar Ehsaan Loy.
Shah Rukh Khan, Kajol.
Dolby digital, PAL, 16.9, Genre Drama, Subtitle in English
Keywords: Muslims -- America -- Attitude -- Drama; Motion Picture; Feature films